Disability and the Meaning of Social Justice in Teacher Education Research: A Precarious Guest at the Table?. (March 2021) - Pugach, Marleen C.; Matewos, Ananya M.; Gomez-Najarro, Joyce
Although disability is assumed to be part of the teacher education social justice landscape, its position in the context of social justice is contested and has not been informed by an analysis of the empirical record. To address this gap, we examined 25 years of research on social justice in teacher education, focusing on how disability is presented in relationship to other social markers of identity. Disability is only modestly visible within this literature; when included, it is typically treated as an isolated marker of identity, absent considerations of intersectionality. Overcoming this marginalization of disability requires new, robust cross-faculty alliances in conceptualizing research on social justice in teacher education; adopting discursive practices that complicate disability in terms of its intersectional, reciprocal relationship with the full range of social markers of identity; and intersectionality-driven instruction connecting multiple identities and the multiple instructional strategies required to transform teacher education for social justice.